Triagem auditiva neonatal: o custo X efetividade de cinco protocolos em uma maternidade de São Paulo - Monteiro, Patricia de Carvalho (2008)
Objective: To investigate the cost x effectiveness of five newborn hearing screening (NHS) protocols in a public hospital in São Paulo. Methods: Clinical outcomes from 2060 newborns, screened during a nine months period, using a protocol of NHS with Transient Otoacoustic Emissions (TEOAE) and Automated Auditory Brainstem Response (AABR). It was possible to analyze five protocols for cost and effectiveness. Protocol 1: UNHS with TEOAE in two stages; protocol 2: UNHS with TEOAE in the first stage, AABR in the second stage; protocol 3: UNHS - neonates without Risk Factors were screened with TEOAE in the first stage and AABR in second stage. Neonates with risk factors were screened only with AABR; protocol 4: Selective NHS (SNHS) - using TEOAE in a combination with AABR in two stages; protocol 5: SNHS - with AABR in two stages. All newborns who referred before discharge should return in 15 days for re-screen. The effectiveness of the protocols was evaluated by the indicators of quality of Joint Committee on Infant Hearing (2007) and the cost was estimated by the proposal of the National Center for Hearing Assessment and Management (2003). Results: The results were presented regarding the percentage of newborns screened, newborns referred for diagnosis and the cost per newborn screened. We found the following results: protocol 1: 92% of newborns screened, 2.1% of newborns referred for diagnosis and cost of $7.53; protocol 2: 88% of newborns screened, 0.5% of newborns referred for diagnosis and cost of $8.9; protocol 3: 86% of newborns screened, 0.6% of newborns referred for diagnosis and cost of $9.16; protocol 4: 71% of newborns screened, 7.3% of newborns referred for diagnosis and cost of $61.1; protocol 5: 71% of newborns screened, 2% of newborns referred for diagnosis and cost of $56.1. Conclusion: The protocol 3 was considered the better for cost and effectiveness in order to identify cochlear hearing loss for newborns without risk factors, and cochlear and retrocochlear hearing loss for neonates with risk factors